Process optimization for bioprotein production from cheaper carbon source - Jamal, Parveen; Alam, Md. Zahangir; Fairoza, N. (Springer Science, 2008)
The rapid population growth in different parts of the world, especially in developing countries, necessitates invention of an alternative protein-rich food source, which is an important dietary component. Agricultural wastes and cheap carbon and high energy sources, for example wheat flour, can be used for producing the value-added bioprotein. A lab scale study was carried out to optimize the process conditions for bioprotein production from a cheaper carbon source (wheat flour) using a potential strain, which was selected earlier by screening different isolated microorganisms. The performance of the selected strain was evaluated by process optimization at various temperatures, pH, agitations and inoculum sizes with fixed media compositions based on our data obtained by media optimization. Central composite design from MINITAB 13.20 software was used and statistical optimization was carried out to evaluate the polynomial regression model through effect of linear, quadratic and interactive factors. The maximum biomass produced was 70.6 (g/L) with optimum fermentation conditions of temperature, pH, agitation, inoculum size and four-day long fermentation.